A real-world pharmacovigilance study of FDA Adverse Event Reporting System (FAERS) events for Definity - Wanting Jiang; Shudan Yin; Lingmin Li; Menghao Teng (PLoS ONE, 2025)
Background Definity significantly enhances the diagnostic accuracy of echocardiography but raises ongoing safety concerns. This study aimed to explore potential adverse events (AEs) associated with Definity in real-world settings by analyzing data from the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS). Methods We retrospectively extracted AE reports from the FAERS database between 2004 and the first quarter of 2024. Disproportionality analyses using reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and multi-item gamma Poisson shrinker (MGPS) were conducted to identify signals potentially associated with Definity. Univariate and multivariate logistic regression analyses were performed as sensitivity analyses to assess potential risk factors for Definity-related AEs. Results A total of 4460 reports with Definity as the “primary suspected” drug were included. We identified 104 statistically significant signals at PT level, including common AEs such as back pain and muscle spasms, as well as exploratory signals not listed on the drug label, such as eye movement disorder and renal pain. It is noteworthy that 21 signals did not retain significance following Bonferroni correction. These AEs spanned 25 System Organ Classes (SOCs). In reports with available time-to-onset data, most events occurred within 30 days of administration, while some were reported at longer intervals. Moreover, logistic regression analysis indicated that both gender and body weight were independent risk factors associated with Definity-related AE. Conclusion This study provides exploratory insights into potential AEs associated with Definity based on real-world pharmacovigilance data. While most signals are consistent with known safety profiles, several emerging signals warrant further investigation and clinical awareness. These findings may contribute to ongoing risk management and pharmacovigilance efforts.